RESEARCH OF EDUCATIONAL INTERPRETATIONS OF THE GREAT POET IN THE RESEARCH OF THE NAVOI SCIENTIST S.OLIMOV (Scientific journal of the Fergana State University, 2022)
This article will talk about the study of the interpretations of Alisher Navoi personality and educational-artistic thinking in the scientific research of the Navoi scientist S.Olimov